1994
DOI: 10.1037/0022-3514.67.3.366
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the "planning fallacy": Why people underestimate their task completion times.

Abstract: This study tested 3 main hypotheses concerning people's predictions of task completion times: (a) People underestimate their own but not others' completion times, (b) people focus on plan-based scenarios rather than on relevant past experiences while generating their predictions, and (c) people's attributions diminish the relevance of past experiences. Results supported each hypothesis. Ss' predictions of their completion times were too optimistic for a variety of academic and nonacademic tasks. Think-aloud pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
702
4
14

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 882 publications
(767 citation statements)
references
References 37 publications
31
702
4
14
Order By: Relevance
“…The study found that those who were required to hand in the assignment (the observers) tended to be overoptimistic, but those who predicted the completion date for another student (the actors) were not [9]. The actors believed they would complete the work an average of 1.3 days earlier than they did.…”
Section: Let Other People Make the Prediction?mentioning
confidence: 97%
See 2 more Smart Citations
“…The study found that those who were required to hand in the assignment (the observers) tended to be overoptimistic, but those who predicted the completion date for another student (the actors) were not [9]. The actors believed they would complete the work an average of 1.3 days earlier than they did.…”
Section: Let Other People Make the Prediction?mentioning
confidence: 97%
“…9 Take home message 2: People have a tendency to give predictions of most likely time usages that are the same or too close to those given when instructed to assume best-case or ideal conditions. In short, what we think is realistic time usage tends to be too close to the best-case time usage.…”
Section: Consider Alternative Futuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Calderson (1993) found that professional financial analysts consistently overestimated the earnings realized. It is interesting to note that many of these optimistic biases occurs even when people acknowledge that many of the predictions made by them in the past were unrealistic (Buehler et al 1994). Optimism is said to stem from both cognitive and motivational sources and I review both these sources in the following section.…”
Section: Influence Of Unrealistic Optimism On Decisionsmentioning
confidence: 99%
“…Such optimism manifests itself in numerous forms. For instance, Buehler, Griffin and Ross (1994) document the planning fallacy, where people expect to finish a personal project in much less time than what it really takes to finish.…”
Section: Influence Of Unrealistic Optimism On Decisionsmentioning
confidence: 99%